Culturable bacterial communities on leaf sheaths and panicles of rice plants in Japan - Shinohara, Hirosuke; Yoshida, Shigenobu; Enya, Junichiro; Watanabe, Yuriko; Tsukiboshi, Takao; Negishi, Hiromitsu; Tsushima, Seiya (Folia microbiologica, 2011)
Culturable bacterial communities on rice plants were investigated from 2001 to 2003. In total, 1,394 bacterial isolates were obtained from the uppermost leaf sheaths at 1 month before heading time and from leaf sheaths and panicles at heading time. The average culturable bacterial population on the leaf sheaths was larger at heading time than at 1 month previously. Furthermore, the population was significantly larger on panicles than on leaf sheaths, suggesting that the bacterial population is influenced by the organs of rice plants. Larger proportions of bacteria were obtained from the macerates of leaf sheaths after washing with phosphate buffer, and most culturable bacteria were verified to inhabit the inside or inner surface, rather than the outer surface, of the tissues. Verification of the bacterial composition based on 16S rRNA gene sequences revealed that genera of Sphingomonas, Microbacterium, Methylobacterium, and Acidovorax tended to be dominant colonizers on leaf sheaths, whereas Pseudomonas and Pantoea were isolated mainly from the panicles, indicating that leaf sheaths and panicles harbor distinct communities. Furthermore, the richness of bacterial genera was less on both leaf sheaths and panicles at heading time compared with that observed 1 month before heading time. Phylogenetic analyses using bacterial isolates belonging to the four dominant genera inhabiting leaf sheaths at heading time revealed that particular bacterial groups in each genus colonized the leaf sheaths.
Keywords: RNA, Ribosomal, 16S; Japonsko; ribozomální DNA; DNA, Bacterial; listy rostlin; RNA ribozomální 16S; DNA, Ribosomal; Oryza; molekulární sekvence - údaje; Japan; Phylogeny; DNA bakterií; Plant Leaves; Molecular Sequence Data; Bacteria; rýže (rod); fylogeneze